FROM DONALD TRUMP TO JOE BIDEN: PSYCHO-SOCIAL AND SPIRITUAL MANAGEMENT OF COVID- 19. Anne Nathalie J. A. AGUESSY ------- - AGUESSY, ANNE NATHALIE JOUVENCIA AGOSSI (My University, 2021)
In the context of the Coronavirus disease (COVID-19), two major speeches have respectively been delivered by the former American president Donald Trump on March 11, 2020 and the current president Joe Biden on March 11, 2021 about the global pandemic, a year later, during the anniversary of Covid-19 shutdown. In fact, at the time of Biden’s address to the Nation, 527, 000 deaths were recorded while in the whole world, the death toll was slightly more than two million, provoking various politics to address their population. The speech of the presidents could have good or bad impact depending on the hidden motivation and /or the personality of the speaker. A big failure is perceived in the management of the Covid- 19 due to a certain type of discourse. To solve this, this problematic style of speaking is compared with another one dealing with the same issue, that is the global pandemic. This paper aims thus to analyze their approaches from the psychological and social standpoints and more importantly and rarely addressed, from the spiritual one, viewed as fundamental for a lasting solution. Comparison and critical approach to the speech confronted with the reality check of the statements will be essential here in the critical analysis of these statements. Another way to solve this problem is the use of the ethical approach to appreciate the genuineness and the relevance of the statement.
Keywords: Covid- 19; psychological management; social management; spiritual; management; pandemic